Epidemiological assessment of eight rounds of mass drug administration for lymphatic filariasis in India: implications for monitoring and evaluation. - Subramanian Swaminathan; Vanamail Perumal; Srividya Adinarayanan; Krishnamoorthy Kaliannagounder; Ravi Rengachari; Jambulingam Purushothaman (Public Library of Science (PLoS), 2012)
BACKGROUND: Monitoring and evaluation guidelines of the programme to eliminate lymphatic filariasis require impact assessments in at least one sentinel and one spot-check site in each implementation unit (IU). Transmission assessment surveys (TAS) that assess antigenaemia (Ag) in children in IUs that have completed at least five rounds of mass drug administration (MDA) each with >65% coverage and with microfilaria (Mf) levels <1% in the monitored sites form the basis for stopping the MDA. Despite its rigour, this multi-step process is likely to miss sites with transmission potential ('hotspots') and its statistical assumptions for sampling and threshold levels for decision-making have not been validated. We addressed these issues in a large-scale epidemiological study in two primary health centres in Thanjavur district, India, endemic for bancroftian filariasis that had undergone eight rounds of MDA. METHODOLOGY/PRINCIPAL FINDINGS: The prevalence and intensity of Mf (per 60 µl blood) were 0.2% and 0.004 respectively in the survey that covered >70% of 50,363 population. The corresponding values for Ag were 2.3% and 17.3 Ag-units respectively. Ag-prevalence ranged from 0.7 to 0.9%, in children (2-10 years) and 2.7 to 3.0% in adults. Although the Mf-levels in the survey and the sentinel/spot check sites were <1% and Ag-level was <2% in children, we identified 7 "residual" (Mf-prevalence ≥ 1%, irrespective of Ag-status in children) and 17 "transmission" (at least one Ag-positive child born during the MDA period) hotspots. Antigenaemic persons were clustered both at household and site levels. We identified an Ag-prevalence of ~1% in children (equivalent to 0.4% community Mf-prevalence) as a possible threshold value for stopping MDA. CONCLUSIONS/SIGNIFICANCE: Existence of 'hotspots' and spatial clustering of infections in the study area indicate the need for developing good surveillance strategies for detecting 'hotspots', adopting evidence-based sampling strategies and evaluation unit size for TAS.